EFEKTIVITAS PEMBELAJARAN MENGGUNAKAN MEDIA ONLINE SELAMA MASA PANDEMI COVID-19 PADA MATA KULIAH ANATOMI FISIOLOGI MULOK - Ajeng Dwi Retnani (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2022)
The Covid-19 pandemic that is currently taking place has brought winds of change in almost all settings, both in terms of economic, socio-cultural, political, health and education aspects. The Hermina Manggala Husada Nursing Academy also follows government policies and in March 2020 issued a circular regarding preventing the spread of the Covid-19 pandemic by changing the learning strategy from face-to-face to online learning. All teaching subjects use online media, one of which is the mulok physiology anatomy course. Changes in this learning method from being conservative to learning using online media will bring significant changes in the learning process. Lecturers as teachers and students must adapt to the obstacles that may arise during the online learning process, both due to internal and external factors. The purpose of this study was to analyze the effectiveness of learning using online media during the Covid-19 pandemic in the mulok physiology anatomy course. The type of research carried out is program evaluation. The evaluation model used in this study is the CIPP (Context, Input, Process, Product). The method used in this research is quantitative with a descriptive approach. The results showed that the location of the student's presence in online learning determines the success and fluency of accessing the internet network. The online learning application that is often used when the subject of anatomy and physiology is mulok is googlemeet. The interest of students in online lectures is also supported by the quality of the teaching materials provided by the lecturers. Learning using googlemeet when the physiology anatomy course is quite effective, seeing that the average UTS score of 68 respondents is 80